HPLC coupled with electrospray ionization multistage MS/MS and TLC analysis of flavones‐C‐glycosides and bibenzyl of Dendrobium hercoglossum. Issue 20 (10th September 2020) - Hu, Li; Zhou, Chujuan; Huang, Yue‐Chun; Wang, Yawen; Wei, Gang; Liang, Zhiyun; Zhou, Chunhua
Abstract: Dendrobium hercoglossum Rchb. f. ( D. hercoglossum ), as one of the origins of medicinal Dendrobium, has been widely used as a health food and nutrient source promoting fluid production. Due to a lack of quality control, it is often counterfeited or mixed with other Dendrobium. In this study, a high‐performance liquid chromatography characteristic chromatogram method is established for the quality evaluation of D. hercoglossum . Based on the high‐performance liquid chromatography characteristic chromatogram, D. hercoglossum is divided into two classes, each with different flavone peaks. These flavone peaks were identified using high‐performance liquid chromatography coupled with electrospray ionization multistage tandem mass spectrometry. Among them, the acylated (3‐hydroxy‐3‐methylglutaryl, p‐coumaroyl, feruloyl, or sinapoyl) flavones‐C‐glycosides are first found in D. hercoglossum in this study. In addition, one unique band was found in D. hercoglossum by thin‐layer chromatography, which can be used to distinguish it from other Dendrobium species as a characteristic marker of this plant. Combining the high‐performance liquid chromatography characteristic chromatogram and high‐performance liquid chromatography coupled with electrospray ionization multistage tandem mass spectrometry, the unique band was identified as 4, 5‐dihydroxy‐3, 3′‐dimethoxybibenzyl. These analysis methods can be applied for the quality control and identification of D. hercoglossum as well as providing reference for the identification of similar constituents in other Dendrobium species.